Perancangan Software Robot Pencari dan Penyusun Menara Lagori pada ABU Robocon 2022 - Salahuddin Ali; Yusman Yusman; Bakhtiar Bakhtiar; Muhammad Raju (Politeknik Negeri Lhokseumawe, 2022)
Lagori is a traditional game and one of the games originating from southern India. This game is played by two teams, where the first team is the seeker and the second team is the pitcher. The game starts by throwing the ball by the seeker to break the stone tower called Lagori. While the seeker tries to pile up more stones, the hitter throws the ball to annoy them. The purpose of this final project is to design a search robot and a Lagori tower to take part in the Indonesian Robot Contest (KRI) 2022. This search robot and Lagori tower are designed based on the Contest procedure using the Atmega2560 microcontroller as a microcontroller, pneumatics are used to pull and remove the gripper, robot The search engine and the Lagori tower use a semi-automatic system, so a wireless joystick is used as a controller, making it easier for users to control it. The results of the search robot and tower testing are in accordance with the algorithm that has been embedded in the 2560, for the pwm setting it varies between 100 and 110 and is used as a speed controller and the robot moves directions such as forward, backward, forward, backward, left, and to the right. The I/O ports on the microcontroller are given logic (logic 1), while for pneumatics repelling and pulling the gripper arm, gripper motors, gripper motors, bohh ball drive motors, and off logic firing motors (logic 0).